2019
DOI: 10.1111/cmi.13066
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the interactions of the environmental hostAcanthamoeba castellaniiwith fungi through the recognition by mannose‐binding proteins

Abstract: Free-living amoebae (FLAs) are major reservoirs for a variety of bacteria, viruses, and fungi. The most studied mycophagic FLA, Acanthamoeba castellanii (Ac), is a potential environmental host for endemic fungal pathogens such as Cryptococcus spp., Histoplasma capsulatum, Blastomyces dermatitides, and Sporothrix schenckii. However, the mechanisms involved in this interaction are poorly understood. The aim of this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 89 publications
(121 reference statements)
1
58
2
Order By: Relevance
“…The amoeba-passaged C. neoformans selected in our study differ from those reported in prior studies [24,39,76] in that they did not increase in virulence. Instead, we observed reductions in murine virulence for two of the isolates studied despite increased capacity to damage macrophages from their long interaction with amoeba.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The amoeba-passaged C. neoformans selected in our study differ from those reported in prior studies [24,39,76] in that they did not increase in virulence. Instead, we observed reductions in murine virulence for two of the isolates studied despite increased capacity to damage macrophages from their long interaction with amoeba.…”
Section: Discussioncontrasting
confidence: 83%
“…The 'amoeboid predator-fungal animal virulence hypothesis' formulates the notion that the capacity for virulence in soil fungi with no need for an animal host arose accidently from the traits for survival against ameboid predators that accidently also functioned as virulence factors for animal infection [12]. Consistent with this notion there is a remarkable concordance between fungal phenotypes that promote survival against amoeba and in animal hosts [14,23] and passage in amoeba is associated with increased virulence for several fungal species [24,39,76]. Analysis of virulence for the amoeba-selected strains described in our study in wax moths revealed no major changes in virulence from the parental strains.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses indicated that S schenckii and S brasiliensis suffered phagocytic events by A castellanii , at a significantly higher rate for S schenckii in the first two hours compared to S brasiliensis. This could be explained by the hypothesis tested by Gonçalves et al that receptors on the surface of the amoeba participate differently in fungal recognition. Amoebae possess a variety of surface proteins, with different affinities for the fungal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Fungus bind to amoeba with implication of mannose‐binding proteins 24 . Therefore, we verified whether the interaction of Tr with A. castellanii occurs through these receptors.…”
Section: Discussionmentioning
confidence: 84%
“…Trophozoites were treated with 1 mmol/L mannose 1 hour before challenging with Tr conidia, and then, phagocytosis, fungicidal activity and exocytosis were analysed as described above (section 2.5 and 2.6). 24 …”
Section: Methodsmentioning
confidence: 99%